Magnetostructural phase transitions and magnetocaloric effect in (Gd5-xScx)Si1.8Ge2.2. (15th February 2018) - Rudolph, Kirk; Pathak, Arjun K.; Mudryk, Yaroslav; Pecharsky, Vitalij K.
Abstract: Future advancements in magnetocaloric refrigeration/heat pumping technologies depend on the discovery of new materials that demonstrate large, tunable magnetocaloric effects (MCEs) in the vicinity of coupled magnetic and structural phase transitions that occur reversibly with minimum hysteresis. With this in mind, we investigate phase transitions, microstructure, magnetic, thermal, magnetocaloric, and transport properties of (Gd5-x Scx )Si1.8 Ge2.2 compounds. Replacement of magnetic Gd with non-magnetic Sc in Gd5-x Scx Si1.8 Ge2.2 increases the ferromagnetic to paramagnetic first order phase transition temperature, TC, with only a minor reduction in MCE when x ≤ 0.2. We also demonstrate that hydrostatic pressure further increases TC and reduces the hysteresis of the first order phase transition in Gd4.8 Sc0.2 Si1.8 Ge2.2 from 7 to 4 K. Temperature-dependent x-ray powder diffraction study of Gd4.8 Sc0.2 Si1.8 Ge2.2 confirms the monoclinic ↔ orthorhombic structural transformation at TC, in agreement with magnetic, calorimetric, and electrical transport measurements. In addition to the substantial magnetocaloric effect, a large magnetoresistance of ∼20% is also observed in Gd4.8 Sc0.2 Si1.8 Ge2.2 for ΔH = 50 kOe in the vicinity of the magnetostructural transition. In a drastic reversal of the initial doping behavior further additions of Sc (x > 0.2) suppress formation of the monoclinic phase, change the nature of the transition from first-to second-order, and reduce both the transition temperature and magnetocaloric effect. Graphical abstract: Image 1